An analysis of earnings and dividend forecasts. - Khor, Su Yin. (2008)
This paper examines the accuracy of earnings forecast made by management of Singapore IPO firms during 1989-1998 and also investigates the factors influencing the accuracy. Furthermore the paper compares the accuracy of earnings forecast with dividend forecast and explore the factors that may conttibute to accuracy of dividend forecasts.